2020
DOI: 10.1021/acsami.0c01074
|View full text |Cite
|
Sign up to set email alerts
|

Bright Blue Light Emission of Ni2+ Ion-Doped CsPbClxBr3–x Perovskite Quantum Dots Enabling Efficient Light-Emitting Devices

Abstract: In recent years, significant advances have been achieved in the red and green perovskite quantum dot (PQD)-based light-emitting diodes (LEDs). However, the performances of the blue perovskite LEDs are still seriously lagging behind that of the green and red counterparts. Herein, we successfully developed Ni2+ ion-doped CsPbCl x Br3–x PQDs through the room-temperature supersaturated recrystallization synthetic approach. We simultaneously realized the doping of various concentrations of Ni2+ cations and modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 42 publications
1
92
0
Order By: Relevance
“…Current studies focus mostly on doping a single‐type of metal ions into the host perovskite NCs, while few research efforts have been made on simultaneously doping more than one type of metal ions into the same perovskite hosts and intra‐particle energy transfer processes. [ 29–30,43–44 ] In particular, despite the high popularities of each dopant on their own, no studies have been reported so far about codoping both Mn 2+ and Yb 3+ ions concomitantly into one perovskite NC sample. Beneficially, compared to solely Mn 2+ doped CsPbCl 3 NCs, the co‐introduction of Yb 3+ dopants may lead to an increased total PL QY while maintaining the large Stokes shift for both Mn‐ and Yb‐emission bands with decreased reabsorption loss.…”
Section: Methodsmentioning
confidence: 99%
“…Current studies focus mostly on doping a single‐type of metal ions into the host perovskite NCs, while few research efforts have been made on simultaneously doping more than one type of metal ions into the same perovskite hosts and intra‐particle energy transfer processes. [ 29–30,43–44 ] In particular, despite the high popularities of each dopant on their own, no studies have been reported so far about codoping both Mn 2+ and Yb 3+ ions concomitantly into one perovskite NC sample. Beneficially, compared to solely Mn 2+ doped CsPbCl 3 NCs, the co‐introduction of Yb 3+ dopants may lead to an increased total PL QY while maintaining the large Stokes shift for both Mn‐ and Yb‐emission bands with decreased reabsorption loss.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, a maximum luminance of 11,800 cd m −2 was yielded, which was among the highest for blue PeLEDs. More recently, Song et al reported that the maximum EQE of Ni 2+ -doped blue CsPbBr 0.99 Cl 2.01 PeLEDs was up to 2.4%, which was the best for blue CsPbX 3 PeLEDs [ 317 ].…”
Section: Strategies To Achieve High-performance Impurity-doped Nanmentioning
confidence: 99%
“…[35][36][37] Doping with metal ions like Cd 2 + , Ni 2 + which are smaller in size than Pb 2 + ion gives an enhancement of 20 folds in PLQY of CsPbCl 3 perovskite NCs. [38,39] To target the extrinsic stability of CsPbX 3 NCs towards heat, moisture, and oxygen, it is necessary to look for the approaches such as encapsulation in a polymer matrix, and developing core-shell structures. [40,41] Intriguingly, it is explored that embedding the CsPbX 3 perovskite NCs into a polymer matrix can improve its long-term stability for several months.…”
Section: Introductionmentioning
confidence: 99%
“…[43] Additionally, it has been proved that doping of sodium to protect CsPb(Br/I) 3 perovskite NCs during encapsulation with Al 2 O 3 to form Na: CsPb(Br/I) 3 @Al 2 O 3 nanocomposites makes them less vulnerable to moisture and light exposure. [44] So far, many approaches have been developed to attain high stability and photoluminescence of CsPbX 3 perovskite NCs like surface passivation, [45][46][47][48] metal doping, [35,36,38,49] modified synthesis procedures, [17,18,50,51] core-shell, [43,44,52] encapsulation, [42,53,54] etc (See Figure 2). These methods are very diverse and their outcomes are much varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation